Religious Tolerance, Social Media and Social-Politics in Indonesia: Exploring of NU Garis Lucu and Catholic Garis Lucu Community - Firmanda Taufiq; Ayu Maulida Alkholid (Vol. 1 No. 1 (2022): Proceeding of International Conference Cultures & Languages 2022, 2022)
The issue of inter-religious tolerance becomes an important issue amid Indonesia's diverse ethnic, religious, racial, and cultural situation. This is because many problems in the name of violence and religious conflicts still occur in Indonesia. For this reason, efforts are needed to minimize and respond to these problems. In this case, social media also has an important role in relations between religious communities. For this reason, it is necessary to explore more deeply how several platforms on social media are campaigning and discussing religious tolerance. This study seeks to explore the NU Garis Lucu and the Catholic Community of Garis Lucu in viewing the landscape of religious tolerance in Indonesia on social media. Through discourse analysis theory, researchers seek to examine how the discourse of religious tolerance is debated in the social media space, which in this case is represented by two media platforms, namely NU Garis Lucu and the Catholic Community of Garis Lucu. The results of this study indicate that media platforms such as NU Garis Lucu and the Catholic Community of Garis Lucu have an important role in spreading the pattern of interaction of religious tolerance in Indonesia. The two platforms become accelerators and seek to counter various frictions and conflicts on social media, especially related to hate speech, hostility in the name of religion, and various issues that trigger conflicts between religious communities.